2022
DOI: 10.1186/s12864-022-08522-8
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene co-expression network indicates that the DYNLL2 is an important regulator of chicken breast muscle development and is regulated by miR-148a-3p

Abstract: Background The characteristics of muscle fibers determine the growth and meat quality of poultry. In this study, we performed a weighted gene co-expression network analysis (WGCNA) on the muscle fiber characteristics and transcriptome profile of the breast muscle tissue of Gushi chicken at 6, 14, 22, and 30 weeks. Results A total of 27 coexpressed biological functional modules were identified, of which the midnight blue module had the strongest cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Among these miRNAs that can bind to circRNAs, miR-206 is an essential regulator of skeletal myoblast differentiation [ 43 , 44 ]. MiR-148a-3p contributes to myoblastic differentiation by targeting DYNLL2 and promoting myosin heavy chain (MYHC) protein expression [ 45 ]. MiR-499-5p can regulate the development of skeletal muscle by regulating muscle gene expression through the NFATc1/MEF2C pathway [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these miRNAs that can bind to circRNAs, miR-206 is an essential regulator of skeletal myoblast differentiation [ 43 , 44 ]. MiR-148a-3p contributes to myoblastic differentiation by targeting DYNLL2 and promoting myosin heavy chain (MYHC) protein expression [ 45 ]. MiR-499-5p can regulate the development of skeletal muscle by regulating muscle gene expression through the NFATc1/MEF2C pathway [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the development of the Gushi chicken breast muscle, these genes may influence intramuscular fat content and fatty acid composition to varying degrees through their involvement in fatty acid oxidation. In addition, within the turquoise module, we identified the DYNLL2 gene, which had previously been established in our earlier research as playing a pivotal role in the proliferation and differentiation of myoblasts in breast muscles [ 43 ]. In this study, the turquoise module housing this gene is not correlated with the traits related to breast muscle fatty acid composition.…”
Section: Discussionmentioning
confidence: 99%
“…In calves, WGCNA identified bta-miR-145 and bta-miR-199a-3p as important hub miRNAs regulating rumen development, immune system, and protein digestion [ 23 ]. This technique also established that DYNLL2 and its target miR-148-3p are important regulators of chicken myogenesis [ 24 ]. In this study, the WGCNA technique revealed key modules and hub genes related to leg muscles of embryos at four different development stages.…”
Section: Discussionmentioning
confidence: 99%